2014
DOI: 10.1044/2014_jslhr-s-12-0269
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Vocal Fold Vibrations in Vocally Healthy Subjects: Analysis With Multi-Line Kymography

Abstract: PURPOSE In this study, the authors aimed to analyze longitudinal data from high-speed digital images in normative subjects using multi-line kymography. METHOD Vocally healthy subjects were divided into young (9 men and 17 women; Mage = 27 years) and older groups (8 men and 12 women; Mage = 73 years). From high-speed digital images of phonation at a conversational frequency kymograms were created at 5 different levels of the vocal fold and were analyzed to determine the opening/closing longitudinal phase differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…5,39 The minor variation in monitored longitudinal level can lead to altered speed quotient, as well. 12,38 Speed quotient mean was smaller in the elderly subjects than young subjects. This age-associated decrease in the speed quotient mean may originate from structural and functional alteration of the vocal fold resulting from geriatric change, leading to the decreased speed of vocal folds returning to the midline.…”
Section: Discussionmentioning
confidence: 80%
See 4 more Smart Citations
“…5,39 The minor variation in monitored longitudinal level can lead to altered speed quotient, as well. 12,38 Speed quotient mean was smaller in the elderly subjects than young subjects. This age-associated decrease in the speed quotient mean may originate from structural and functional alteration of the vocal fold resulting from geriatric change, leading to the decreased speed of vocal folds returning to the midline.…”
Section: Discussionmentioning
confidence: 80%
“…In this study, the open quotient was found to be 0.55 ± 0.15 at a speaking F 0 at the midpoint of the membranous portion, which generally matched the values in some previous reports, 23,28,31,38,39 but was rather smaller than those in other reports (Table 7). 5,20 These differences may stem from differences in the data acquisition technique (videostroboscopy 23,39 or HSDI 28,31,38 ), the method of analysis (DKG, 31,38 glottal width waveform, 5 or glottal area waveform 39 ), monitored longitudinal level, 12,38 or variation in the examination conditions. According to previous reports, open quotient increases as F 0 increases and decreases as the intensity increases.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations